Developing E-Reading Materials for Students at Grade Seven: Mengembangkan Materi E-Reading untuk Siswa Kelas Tujuh - Hidayat, Nur (JEES (Journal of English Educators Society), 2017)
The application of Curriculum 2013 influenced teaching learning process in schools. Some hours of technology and English subjects in junior high school are decreased. The materials from English book that provided by the government especially for reading are too simple. It needs supplement materials to support the students’ ability in English. The researcher does 4 steps to product the supplement materials, they are: Need Analysis, Identifying the Syllabus, Developing the Material, Expert’ Reviews and Product Try-out. The supplement product aboard with the following criteria: (1) the content is relevant with Curriculum 2013 and students’ level; (2) the procedure in operating is easier for the students; (3) the exercises and feedbacks are clear and relevant with the content; (4) The design is attractive and interesting; (5) the materials should be practical for the students. The materials are found acceptable and appropriate for students at seven grade level as supplement materials.